Study of Hybrid PV-Wind Energy System to Isolated Micro-grid - Samir M. Dawoud; Xiangning Lin (Institute of Advanced Engineering and Science, 2015)
The optimal sizing of the isolated hybrid microgrid using an optimization technique was proposed. The hybrid system features WT, PV and conversion systems were used to feed the electrical load demand. A HOMER software was used to model system performance during a time of one year, considering Sensitivity variations in both the availability of renewable energy sources and variations in the load demand. The optimal solution was obtained with respect to decrease the cost of energy (COE) and the loss of power supply probability (LPSP) over a project lifetime of 25 years to improve the isolated operation of the microgrid. The aim of this study is to investigate an optimum combination of different energy systems which can supply electricity to a rural area in Egypt. The results show the COE for the optimal model was found 0.139 /kWh which is less than half of the PV or WT system.